WISMA ATLET DI SPORT CENTER KALIMANTAN SELATAN - Muhammad Yusuf Tahmidillah; Bani Noor Muchamad (ULM Press, 2021)
Greenhouse Gas (GHG) emissions are a trigger for global change and excessive use of energy in buildings. The design focuses on the design of the athlete's homestead that is able to be an answer to sustainable design and faces resource problems, especially energy. In achieving sustainability goals and answering architectural problems, the athlete's guesthouse design applies 5 principles of a holistic approach to green buildings and the concept of sustainable architecture as an effort to minimize the negative impact of designs that are able to deal with current crisis conditions such as the energy crisis, greenhouse gas emissions, the environment to the economy. Qualitatively and quantitatively based on the results of the analysis and supporting theories.